Characteristics of adult‐ compared to childhood‐onset type 1 diabetes. Issue 12 (21st May 2020) - Casu, A.; Kanapka, L. G.; Foster, N. C.; Hirsch, I. B.; Laffel, L. M.; Shah, V. N.; DeSalvo, D. J.; Lyons, S. K.; Vendrame, F.; Aleppo, G.; Mastrandrea, L. D.; Pratley, R. E.; et al.
Abstract: Aims: To compare diagnosis characteristics, diabetes management and comorbidities in a population diagnosed with type 1 diabetes in childhood with those in a similar population diagnosed in adulthood to identify disease differences related to the age of diabetes onset. Methods: This analysis was performed using the T1D Exchange Clinic Registry, a cross‐sectional survivor cohort. Retrospectively collected characteristics were compared across the following age‐at‐diagnosis groups: <10, 10–17, 18–24, 25–39 and ≥40 years. Results: The entire cohort included 20 660 participants [51% female, median (interquartile range) age 18 (14–36) years, 82% non‐Hispanic white]. Diabetic ketoacidosis at diagnosis was more common among those with onset in childhood. Participants diagnosed as adults were more likely to be overweight/obese at diagnosis and to have used oral agents preceding type 1 diabetes diagnosis (57%). Current insulin pump use was less frequent in participants diagnosed at older ages. Current glycaemic control, measured by HbA1c, insulin requirements and use of a continuous glucose monitor were not different by age at diagnosis. Coeliac disease was the only comorbidity that was observed to have a different frequency by age at diagnosis, being more common in the participants diagnosed at a younger age. Conclusions: These results show differences and similarities between type 1 diabetes diagnosed in childhood vs adulthood; notably, there was a tendency for there was a higher frequency of diabetic ketoacidosis at onset in children and a higher frequency of use of oral antidiabetes agents in adults. The data indicate that there is little distinction between the clinical characteristics and outcomes of type 1 diabetes diagnosed in childhood vs adulthood. Optimizing glycaemic control remains a challenge in all age groups, with lower use of insulin pumps impacting those diagnosed as adults. What's new?: Data obtained from a large database of autoimmune diabetes cases in the USA confirmed that treatment with oral agents before diagnosis, overweight/obesity, and absence of diabetic ketoacidosis were more frequent when diagnosis occurred in adulthood compared to childhood. HbA1c, use of continuous glucose monitoring, total daily insulin and other comorbidities were not associated with age at onset, while insulin pump use and coeliac disease were less common in adult‐onset diabetes. Once autoimmune diabetes is properly diagnosed and established there is little distinction between outcomes across ages at clinical diagnosis.